Investigation of the effects of intermediate reservoirs and intermediate feedings applications on the performance of proton exchange membrane fuel cells - Celik, Erman; Karagoz, Irfan (Elsevier Sci Ltd, 2023)
This study presents the design principles and details of a new flow field based on the shape and reflex similarity of the circulatory systems of living things. This design has intermediate reservoirs that collect and distribute the flow channels and also allow for intermediate feedings. This design is applied to a proton exchange membrane fuel cell, and its performance is tested and compared with a conventional serpentine type of flow channel. The novel fuel cell with intermediate reservoirs reaches a current density of 0.171 A/cm2 at 0.406 V and displays a power density 10 % higher than the serpentine flow field. Moreover, eleven cases involving symmetrical and asymmetrical feeding arrangements are also examined. The case of 70 %, 20 % and 10 % symmetrical feeding at the main and intermediate inlets shows the highest performance by providing a 38 % higher power density compared to the serpentine flow field.
Keywords: Hydrogen energy; Energy efficiency; Fuel cell; Sustainable energy; Water management